Choreo-athetosis with severe thyrotoxicosis. Issue 649 (November 1979) - Marks, Peter; Anderson, John; Vincent, Richard
Abstract : Two cases of severe thyrotoxicosis are described. They both exhibited choreo-athetoid movements which were abolished by successful treatment of the thyrotoxicosis. It is suggested that the tremor of mild thyrotoxicosis is one end of a spectrum at which choreo-athetosis is at the most severe end. A tentative explanation of this hypothesis is given in the discussion.